Evolutionary steps of sex chromosomes are reflected in retrogenes - Mc Lysaght, Aoife (My University, 2008)
It has been shown that selective pressure to compensate for the silencing of the sex chromosomes during male meiosis resulted in many X-linked genes being duplicated as functional retrogenes on autosomes. Sex chromosome silencing in males was probably stratified during evolution, in accordance with the stratified diversification of the sex chromosomes. Here I show that the timing of the retrocopying events is associated with the timing of the X-Y differentiation of the region of X chromosome housing the parental copy of the gene.
PUBLISHED
Keywords: Genetics; X-Y differentiation; Genes & Society